PENGARUH PROMOSI PENJUALAN, KEPERCAYAAN, DAN PENGGUNAAN BRAND AMBASSADOR K-POP IDOL TERHADAP MINAT BELI KONSUMEN PADA MARKETPLACE SHOPEE - Afna Aisyiah Ainurzana; Jemadi Jemadi (Universitas Nusa Cendana, 2023)
This study aims to determine the effect of Sales Promotion, Trust, and the use of K-pop idol Brand Ambassador on Consumer Buying Interest in the Shopee marketplace. This study used a sample of 100 respondents who had shopped at Shopee at least once. The sampling technique is non-probability sampling with the purposive sampling method. This research data collection method uses a questionnaire which is measured by a Likert scale. The data analysis technique uses multiple regression. The instrument test in this study uses the validity and reliability test. Testing the hypothesis in this study using the t-test and F-test. Data analysis was performed using the SPSS program 25.0 version. The results of this study indicate that Sales Promotion and Trust partially had a positive and significant effect on Consumer Buying Interest in the Shopee marketplace. Meanwhile, K-pop idol Brand Ambassador had a positive but not significant effect on Consumer Buying Interest in the Shopee marketplace. Simultaneously, Sales Promotion, Trust, and K-pop idol Brand Ambassador had a positive and significant effect on Consumer Buying Interest in the Shopee marketplace. Keywords: Sales Promotion; Trust; Brand Ambassador; Buying Interest